Ascensão de João Doria e Romeu Zema em São Paulo e Minas Gerais e a crise do PSDB como intermediário das classes dominantes - Coraccini, Raphael Picolo (2022)
The general goal of this text is to study the rise and fall movement of what will be called here as intermediaries of the political interests of the country's ruling classes, and the consequent rise of members of these ruling classes to prominent positions in institutional policy, specifically focusing on the 2018 elections in the scope of the State Executive of the federative units of Minas Gerais and São Paulo, where the Partido da Social Democracia Brasileira - PSDB was sovereign in part of the 1990s, 2000s and part of the 2010s. The proposal is to investigate the loss of capacity the intermediation of bourgeois interests in the institutional sphere by the PSDB and the existing conditions for the rise of two specific names: entrepreneurs João Dória Jr. (Grupo Lide) and Romeu Zema (Grupo Zema)